An early warning for better planning of agricultural expansion and biodiversity conservation in the Orinoco high plains of Colombia - González-Orozco, Carlos E.; Diaz-Giraldo, Raul Alejandro; Rodriguez-Castañeda, Catalina (Frontiers in Sustainable Food Systems, 2023)
The eastern high plains of the Orinoco region in Colombia are known as "Altillanura". They are considered the future agricultural frontier of Colombia. Unfortunately, an agricultural expansion without taking in consideration areas of high biodiversity and conservation of fragile ecosystems that are ecologically irreplaceable will likely fail in providing a sustainable grow. An orderly management planning of the territory based on scientific evidence is currently lacking for this region. Specifically, studies that combine biodiversity data and agricultural information are a major research gap. This study analyses the spatial patterns of species richness and endemism of flora and fauna at the site and subregional levels. We compared the spatial changes of biodiversity patterns with aspects related to the expansion of the agricultural frontier and its possible impacts. We found a west-to-east pattern; sites closer to the Andes were more exposed to ecological degradation than those in the east. Santa Rosalía and Puerto Lopez are the municipalities with the most remarkable species diversity. Conversely, La Primavera municipality has the most significant number of endemic species. Our spatial changes results raise the alarm showing that hotspots of diversity closer to the municipalities of Puerto Lopez and Puerto Gaitan are under more pressure than underdeveloped municipalities (La Primavera and Puerto Carreño). Our results could serve as a baseline to identify spatial changes of agrobiodiversity and a guideline for land-use planning, regional policies and local decision-makers to improve regional development in Colombia's eastern plains region.